2005
DOI: 10.1111/j.1471-4159.2005.03340.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel multifunctional neuroprotective iron chelator‐monoamine oxidase inhibitor drugs for neurodegenerative diseases: in vitro studies on antioxidant activity, prevention of lipid peroxide formation and monoamine oxidase inhibition

Abstract: Iron-dependent oxidative stress, elevated levels of iron and of monoamine oxidase (MAO)-B activity, and depletion of antioxidants in the brain may be major pathogenic factors in Parkinson's disease, Alzheimer's disease and related neurodegenerative diseases. Accordingly, iron chelators, antioxidants and MAO-B inhibitors have shown efficacy in a variety of cellular and animal models of CNS injury. In searching for novel antioxidant iron chelators with potential MAO-B inhibitory activity, a series of new iron ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
168
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(177 citation statements)
references
References 68 publications
(166 reference statements)
8
168
0
1
Order By: Relevance
“…A series of 8-hydroxyquinoline analogues (VK-28, HLA-20 and MA-30) (Fig. 4) have shown the greatest potential for the treatment of several neurodegenerative diseases (61) and one of these compounds, clioquinol (PBT1, Fig. 5), reached the pilot phase II clinical trial (62)(63)(64)(65)(66), which suggests that clioquinol improves cognition and lowers plasma levels of Ab42 in some patients.…”
Section: Metals Chelators For the Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…A series of 8-hydroxyquinoline analogues (VK-28, HLA-20 and MA-30) (Fig. 4) have shown the greatest potential for the treatment of several neurodegenerative diseases (61) and one of these compounds, clioquinol (PBT1, Fig. 5), reached the pilot phase II clinical trial (62)(63)(64)(65)(66), which suggests that clioquinol improves cognition and lowers plasma levels of Ab42 in some patients.…”
Section: Metals Chelators For the Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…Neurosci. (2010), 1, 737-746 pubs.acs.org/acschemicalneuroscience Article production of ROS, as well as a potent scavenger to scavenge radicals (33,34). It have been shown that the combination treatment of a metal chelator and a radical scavenger protect brain tissue from OS to a greater degree than is achievable with either of them.…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible nonselective MAO-A and -B in liver and intestine is associated with "cheese effect", a sharp elevation in blood pressure that may be life-threatening (48,49). HLA20, possessing a neuroprotective moiety (a propargylamine) from anti-Parkinson's drug rasagiline, is a weak MAO-A/B inhibitor in vitro with a 66.21% and 33.21% inhibition for MAO-B and MAO-A, respectively, at a concentration of 100 μM (34). Attachment of a dimethyl carbamyl moiety at the 8-hydroxyl oxygen in HLA20 slightly increases the inhibitory activity as seen with HLA20A (about 9% and 5% inhibition of MAO-B and MAO-A, respectively, at a concentration of 10 μM in vitro).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations